ECONOMY AND ENVIRONMENTAL SAFETY IN KYRGYZSTAN - Shabieva N.B. (Vestnik Issyk-Kulʹskogo universiteta)
Energy production and consumption affect the health of the world's population and pose environmental challenges. The most dangerous consequences include air and water pollution, climate change and the accumulation of toxic waste. The need for energy supply is growing, and with it the burden on the environment. In this article, we examine the current environmental situation in the world and in Kyrgyzstan and suggest ways to improve it. Black coal occupies the largest share in the use of energy resources in our country. From the reports of the National Statistics Committee, we see that the volume of consumption is rapidly increasing due to the growth of living conditions and the population. In the context of the national economy, we are going to suggest ways to reduce the use of "dirty" energy sources and the possibility of switching to other ecological types.